ANALISI INTEGRASI PRODUKSI DAN HARGA JAGUNG PIPILAN ( Zea mays L) DI KABUPATEN OKU TIMUR (JASEP, 2021)
Analysis of Production Integration and Pipilan Corn Price (Zea mays L) in East OKU Regency. This study aims to analyze the level of integration of corn production and price in East OKU Regency. This research was conducted in OKU Timur Regency with the consideration that in OKU Timur Regency is the center of corn planting.The method used in this research is literature study method. The author uses secondary data about the production and price of corn pipines per year starting from 2011 to 2015. Data collection is done gradually by taking data in Dina Food Crops OKU Timur Regency, Food Security Agency of East OKU Regency, Central Statistics Agency of East OKU Regency, and quoting from scientific journals and various references. In this research data is processed with Eveiws 7 version analysis tool which is a model to analyze time series data. The results showed that maize production and price in East OKU district indicated that the coefficient value of less than one indicates an integration between production and price of corn in Eastern OKU but weakly integrated. This is similar to the Ogantarah study. (2016), which examines the integration of corn production and price of corn in OKU Regency and analysis results indicate that between the production and the price of pipelines is weak integration because the coefficient shows the value of less than one (1). Keyword: Corn, Integration, Production, Price